Age- and sex-specific reference values of biventricular flow components and kinetic energy by 4D flow cardiovascular magnetic resonance in healthy subjects - Zhao, Xiaodan; Tan, Ru-San; Garg, Pankaj; Chai, Ping; Leng, Shuang; Bryant, Jennifer Ann; Teo, Lynette L.S.; Yeo, Tee Joo; Fortier, Marielle V.; Low, Ting Ting; Ong, Ching Ching; Zhang, Shuo; et al. (Journal of cardiovascular magnetic resonance, 2023)
Advances in four-dimensional flow cardiovascular magnetic resonance (4D flow CMR) have allowed quantification of left ventricular (LV) and right ventricular (RV) blood flow. We aimed to (1) investigate age and sex differences of 4D flow CMR-derived LV and RV relative flow components and kinetic energy (KE) parameters indexed to end-diastolic volume (KEiEDV) in healthy subjects; and (2) assess the effects of age and sex on these parameters. We performed 4D flow analysis in 163 healthy participants (42% female; mean age 43 ± 13 years) of a prospective registry study (NCT03217240) who were free of cardiovascular diseases. Relative flow components (direct flow, retained inflow, delayed ejection flow, residual volume) and multiple phasic KEiEDV (global, peak systolic, average systolic, average diastolic, peak E-wave, peak A-wave) for both LV and RV were analysed. Compared with men, women had lower median LV and RV residual volume, and LV peak and average systolic KEiEDV, and higher median values of RV direct flow, RV global KEiEDV, RV average diastolic KEiEDV, and RV peak E-wave KEiEDV. ANOVA analysis found there were no differences in flow components, peak and average systolic, average diastolic and global KEiEDV for both LV and RV across age groups. Peak A-wave KEiEDV increased significantly (r = 0.458 for LV and 0.341 for RV), whereas peak E-wave KEiEDV (r = − 0.355 for LV and − 0.318 for RV), and KEiEDV E/A ratio (r = − 0.475 for LV and − 0.504 for RV) decreased significantly, with age. These data using state-of-the-art 4D flow CMR show that biventricular flow components and kinetic energy parameters vary significantly by age and sex. Age and sex trends should be considered in the interpretation of quantitative measures of biventricular flow. Clinical trial registration https://www.clinicaltrials.gov. Unique identifier: NCT03217240.